Brincar na prática assistencial de técnicos de enfermagem em unidade pediátrica hospitalar - Petruccelli, Gabriele (Universidade Federal de São Carlos, 2025)
Article 1. Petruccelli G, Wernet M, Silveira AO, Maia EBS. Play in the care practices of nursing technicians with hospitalized children. Rev Gaúcha Enferm. 2025;46:e20240348. https://doi.org/10.1590/1983-1447.2025.20240348.pt Objective: to understand the use of play in the care practices of licensed practical nurses with hospitalized children. Method: this is a qualitative, exploratory and descriptive study, based on the Symbolic Interactionism theoretical-methodological framework, developed in a pediatric inpatient unit of a university hospital located in the countryside of São Paulo. Data was collected from August to October 2023 using non-participant observation. The study included 25 licensed practical nurses working in the unit in question. Data analysis was based on reflective thematic analysis. Results: play was primarily used to facilitate the execution of procedures. It was evident that participants did not link and integrate this resource into their care practices. Furthermore, the toy library was not understood as a space associated with licensed practical nurses. The themes “Play in care practices” and “Interactions with the hospital toy library” detail the professional practices observed. Conclusion: the use of play in licensed practical nurses’ care practices was reinforced by the symbolism that play is not feasible during pediatric hospitalization and that using the toy library is not part of its scope, which determined the limited incorporation of this resource. Furthermore, the importance of play activities was not recognized by the participants. Article 2. Petruccelli G, Wernet M, Silveira AO, Maia EBS, Almeida CL, Loureiro FM. Nursing technicians’ perceptions about the use of play and playfulness in professional practices. Article accepted for publication in the Rev Esc Enferm USP on 08 de abril de 2025. Objective: to understand nursing technicians’ perceptions in a pediatric inpatient unit regarding the use of play and playfulness in their professional practices. Method: an exploratory study with a qualitative approach, supported by the Symbolic Interactionism theoretical framework, developed in a pediatric unit of a university hospital in the countryside of São Paulo. Data collection took place from March to December 2024, through semi-structured interviews, with 14 participants. Reflective thematic analysis supported data assessment. Results: the topics “Purposes of adopting play and playfulness” and “Determinants of adopting play and playfulness” revealed that nursing technicians link resources with the execution of technical procedures and formation of bonds. However, they highlighted a context that was not very supportive of this use and that led to the meaning that these resources were other professionals’ responsibility. Conclusion: the use of play and playfulness predominated for the execution of procedures, with a secondary, informal, voluntary and non-institutionalized place in nursing care for children. Article 3. Petruccelli G, Wernet M, Maia EBS, Bonelli MA, Pimenta NAC, Santos BP. Nursing technicians' perceptions of the hospital toy library and their work in this environment. Article submitted to Revista Mineira de Enfermagem on 09/02/2025. Objective: to find out the nursing technicians’ perceptions in a pediatric inpatient unit about the hospital toy library and their work in this environment. Method: an exploratory study with a qualitative approach, supported by the Symbolic Interactionism theoretical framework. It was developed in a pediatric unit of a university hospital located in a countryside in the interior of São Paulo. Data collection took place from March to December 2024, trough semi-structured interviews. Fourteen nursing technicians took part in the study. Reflective thematic analysis supported data assessment. Results: the nursing technicians considered the toy library to be an essential space in pediatric units, with contributions to coping with hospitalization. They relativized the space as belonging to their professional scope, despite revealing a desire to be trained to be in this environment, as well as showing positions about its operationalization. The topics “Symbolisms and use of the toy library by nursing technicians”, “Toy library and the scope of the nursing technician profession”, “Control in the toy library”, and “Gaps in institutional support for the use of the toy library” revealed the perceptions about the place and the technician's role in it. Conclusion: we noted the presence of the symbolism that the toy library is an extremely important place in the pediatric hospitalization unit. Its contributions include making it easier to carry out procedures, facilitating recovery and treatment, and carrying the symbol of lightness in a hostile environment. On the other hand, the nursing technicians do not recognize the toy library as an environment in which they are responsible.

Artículo 1. Petruccelli G, Wernet M, Silveira AO, Maia EBS. El juego en las prácticas asistenciales de los enfermeros no diplomados con los niños hospitalizados. Rev Gaúcha Enferm. 2025;46:e20240348. https://doi.org/10.1590/1983-1447.2025.20240348.pt Objetivo: comprender el uso del juego en las prácticas de cuidado de los enfermeros no diplomados con niños hospitalizados. Método: se trata de un estudio cualitativo, exploratorio y descriptivo, basado en el marco teórico-metodológico del Interaccionismo Simbólico, desarrollado en una unidad de internación pediátrica de un hospital universitario localizado en el interior de São Paulo. Los datos fueron recolectados de agosto a octubre de 2023 mediante observación no participante. Participaron del estudio 25 técnicos de enfermería que trabajaban en la unidad en cuestión. Los datos fueron analizados por medio del análisis temático reflexivo. Resultados: el uso del juego se utilizó más específicamente para favorecer la ejecución de procedimientos. Se evidenció que los participantes no vincularon e integraban este recurso en sus prácticas de cuidado. Además, la ludoteca no fue entendida como un espacio asociado al enfermero no diplomado. Los temas “El juego en las prácticas de cuidado” e “Interacciones con la ludoteca hospitalaria” detallan las prácticas profesionales observadas. Conclusión: el uso del juego en las prácticas asistenciales de los enfermeros no diplomados se vio reforzado por el simbolismo de que el juego no es viable durante la hospitalización pediátrica y que el uso de la ludoteca no forma parte de su ámbito, lo que determinó la incorporación lacunar de este recurso. Además, la importancia del juego no fue reconocida por los participantes. Artículo 2. Petruccelli G, Wernet M, Silveira AO, Maia EBS, Almeida CL, Loureiro FM. Percepciones de las técnicas de enfermería sobre el uso del juego y el entretenimiento en las prácticas profesionales Artículo aceptado para publicación em la Rev Esc Enferm USP en 08 de abril de 2025. Objetivo: comprender las percepciones de las técnicas de enfermería de una unidad de internación pediátrica sobre el uso del juego en sus prácticas profesionales. Método: estudio exploratorio con abordaje cualitativo, sustentado en el referencial teórico del Interaccionismo Simbólico, desarrollado en una unidad pediátrica de un hospital universitario del interior de São Paulo. La recolección de datos se realizó de marzo a diciembre de 2024, mediante entrevistas semiestructuradas, con 14 participantes. El análisis temático reflexivo apoyó la evaluación de los datos. Resultados: los temas “Propósitos de la adopción de actividades lúdicas y recreativas” y “Determinantes de la adopción de actividades lúdicas y recreativas” revelaron que las técnicas de enfermería vinculan los recursos a la ejecución de procedimientos técnicos y a la formación de vínculos. Sin embargo, pusieron de relieve un contexto poco favorable a este uso y que llevó a que el significado de estos recursos quedara al alcance de otros profesionales. Conclusión: el uso del juego y actividades recreativas predominó en la ejecución de los procedimientos, teniendo un lugar secundario, informal, voluntario y no institucionalizado en la atención de enfermería al niño. Artículo 3. Petruccelli G, Wernet M, Maia EBS, Bonelli MA, Pimenta NAC, Santos BP. Percepciones de las técnicas de enfermería sobre la ludoteca hospitalaria y su desempeño en este entorno. Artículo enviado a la Revista Mineira de Enfermagem en 09/02/2025. Objetivo: comprender las percepciones de las técnicas de enfermería de una unidad de internación pediátrica sobre la ludoteca hospitalaria y su trabajo en este entorno. Método: estudio exploratorio con abordaje cualitativo, sustentado en el referencial teórico del Interaccionismo Simbólico. Fue desarollado en una unidad de internación pediátrica de un hospital universitario localizado en un municipio del interior del estado de São Paulo. La recolección de datos se realizo de marzo a diciembre de 2024, mediante entrevistas semiestructuradas. Catorce técnicas de enfermería participaron en la investigación. El análisis temático reflexivo apotó la evaluación de los datos. Resultados: las técnicas de enfermería consideraron la ludoteca como un espacio esencial en las unidades pediátricas, con contribuciones al afrontamiento de la hospitalización. Relativizaron el espacio como perteneciente a su ámbito profesional, a pesar de revelar su deseo de ser formados para trabajar en este ambiente, así como sus posiciones sobre su operacionalización. Los temas “Simbolismo y uso de la ludoteca por las técnicas de enfermeira”, “Ludoteca y ámbito de la profesión de técnico de enfermeira”, “Control en la ludoteca” y “Lagunas en el apoyo institucional al uso de la Ludoteca” retratan las percepciones sobre el lugar y el papel del técnico en él. Conclusión: se constató el simbolismo de la ludoteca como lugar de extrema importancia en la unidad de internación pediátrica. Entre sus contribuciones se encuentran facilitar los procedimientos, favorecer la recuperación y el tratamiento, y portar el símbolo de la ligereza en un entorno hostil. Por otro lado, las técnicas de enfermería no reconocen la sala de juguetes como un área de su responsabilidad y actividad.
Play in the care practices of nursing technicians in a pediatric inpatient unit
El juego en las prácticas asistenciales de los enfermeros no diplomados en una unidad de internación pediátrica
Keywords: Jogos e brinquedos; Enfermagem pediátrica; Hospitalização; Criança; Técnicos de enfermagem; Centros de convivência e lazer; Play and playthings; Pediatric nursing; Hospitalization; Child; Licensed practical nurses; Centers of connivance and leisure; Juego e implementos de juego; Enfermería pediátrica; Hospitalización; Niño; Enfermeros no diplomados; Centros de ocio y convivencia; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM PEDIATRICA